History of childhood maltreatment is associated with reduced fractional anisotropy of the accumbofrontal 'reward' tract in healthy adults. - DeRosse, Pamela; Ikuta, Toshikazu; Karlsgodt, Katherine H.; Szeszko, Philip R.; Malhotra, Anil K. (Brain Imaging & Behavior, 2020)
The deleterious outcomes associated with exposure to childhood maltreatment (CM) are well known and may be at least partially mediated by self-harm behaviors. It has been suggested that these self-harm behaviors serve as a means of decreasing negative mood states but the effects of CM on health outcomes may be much more sinister. A wealth of data suggest that CM may lead to experience-dependent changes in neural circuits underlying reward processes; processes associated with many harmful behaviors. The present study examined the relationship between a history of CM and the microstructure of a white matter tract that may be central to reward processes. Healthy adults (N = 122) were assessed with a diffusion tensor imaging (DTI) exam and the Childhood Trauma Questionnaire (CTQ). Probabilistic tractography was used to delineate the accumbofrontal "reward" tract, connecting the orbitofrontal cortex and nucleus accumbens, and measures of white matter microstructure were extracted. We then examined whether variation in CTQ scores were associated with variation in the microstructure of this tract as measured by fractional anisotropy (FA). After accounting for the effects of age and sex, the CTQ total score accounted for approximately 6% of the variance of FA in the accumbofrontal tract (F(3, 121) = 5.74; p = .001). Post hoc analyses indicated that the overall severity of CM, rather than a specific type of maltreatment, drove this result. These findings indicate that CM influences white matter microstructure in a fiber tract that is likely central to reward processes and adds to a growing literature implicating CM in long-term health-related outcomes.